Preperation of Thin Film of Tin Oxide (SnO2) by Spray Pyrolysis Method and Study its Application as Gas Sensor - Chalise, R.; Thakur, P. K.; Nakarmi, J. J.; Shrestha, S. P. (Journal of Nepal Physical Society, 2021)
In this article SnO2 thin films have been deposited onto glass substrates by Spray Pyrolysis Method. Tin chloride dihydrate (SnCl2.2H2O) and Copper nitrate (Cu (NO3)2 .3H2O) were used as source of Sn and Cu respectively. The structural, optical and gas sensing properties of Undoped and copper doped by (vol. %) SnO2 film have been investigated. XRD of film shows structure of films. Also result so obtained from XRD spectroscopy shows that these layers have the tetragonal polycrystalline tinoxide structure. The optical transmission was found to decrease with addition of copper as dopant on SnO2 with the addition of Cu except for 5% Cu-Doped. The reponse of these layers have been investigated for different concentrations of butane gas by static gas sensing system. The results of this investigation show that the Cu-Doped SnO2 nanostructure layer compared with the pure SnO2 nanostructure layer has showed the better response for butane gas. Among Cu-Doped SnO2 thin film layer 4% (by vol.) copper doped thin film layer has showed higher response toward the Butane gas with less response and recovery time than other films.